ELECTROMECHANICAL PROPERTIES OF SELF-SENSING CEMENT PASTES POLARIZED WHILE FRESH - Al-Qaralleh, Mohammad (Journal of Applied Engineering Science, 2023)
This work investigates the bulk resistivity, and the stress-strain relationship of polarized cement paste as indicators of its electromechanical properties. The polarizing of the cement paste specimens was achieved by applying a uniform direct current (DC) electric field through the fresh cement paste for 24 hours. A total of 24 specimens were prepared for this study, 7 of them were not cured under the effect of the DC electric field to serve as reference. 3 different electrical field values were utilized in this experiment, namely: 100 V.m-1, 200 V.m-1, and 500 V.m-1. 2 types of water were used for mixing the cement paste, namely: tap (T), and deionized (DI). The bulk resistivity values were measured in the direction parallel to the polarization, and the two other directions perpendicular to the polarization. The T water specimens were tested under uniaxial compression on the axis of polarization. The results show that the bulk resistivity of the specimens was increased as the curing electrical field increased. Mixing with T water also increased the bulk resistivity when compared to mixing with DI water. Polarizing the fresh cement paste has a significant effect on its mechanical properties such that the ultimate compressive strength decreased by 50%, and the failure strain increased by 500%. In addition, the polarized specimens showed some changes in its morphology when compared with the reference.
Keywords: polarizing, fresh cement paste, self-sensing, bulk resistivity, structural health monitoring (SHM)